Sorption isotherm modeling of “gaplek” flour fortified by protein from red bead tree flour - Margareta Novian Cahyanti; Alvama Pattiserlihun (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2018)
The objective of the study is to determine the characteristic of moisture sorption isotherm from